2001
DOI: 10.1104/pp.126.3.1162
|View full text |Cite
|
Sign up to set email alerts
|

Binding Site for Chitin Oligosaccharides in the Soybean Plasma Membrane

Abstract: Affinity cross-linking of the plasma membrane fraction to an 125 I-labeled chitin oligosaccharide led to the identification and characterization of an 85-kD, chitin binding protein in plasma membrane-enriched fractions from both suspension-cultured soybean cells and root tissue. Inhibition analysis indicated a binding preference for larger (i.e. degrees of polymerization ϭ 8) N-acetylated chitin molecules with a 50% inhibition of initial activity value of approximately 50 nm. N-Acetyl-glucosamine and chitobios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 42 publications
3
77
0
Order By: Relevance
“…Similarly, the availability of chitinases and other chitin hydrolytic or binding activities in the plant cell wall could drastically reduce the elicitor concentration effectively perceived by the protoplast. The level of expression of oligochitin receptors (Bradley Day et al 2001, Okada et al 2002, or of other oligochitin-binding proteins Claeson 2003, Peumans et al 2003), could be developmentally regulated and also explain the discrepancies between different plant models (cell suspensions, seedlings and whole plants) and plant species. For example, Okada et al (2002) showed that carrot, wheat, barley, rice and tobacco BY-2N cells responded differently to N-acetyl-chitooligosaccharides, although their plasma membranes all contained a high-affinity binding site for N-acetyl-chitooligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the availability of chitinases and other chitin hydrolytic or binding activities in the plant cell wall could drastically reduce the elicitor concentration effectively perceived by the protoplast. The level of expression of oligochitin receptors (Bradley Day et al 2001, Okada et al 2002, or of other oligochitin-binding proteins Claeson 2003, Peumans et al 2003), could be developmentally regulated and also explain the discrepancies between different plant models (cell suspensions, seedlings and whole plants) and plant species. For example, Okada et al (2002) showed that carrot, wheat, barley, rice and tobacco BY-2N cells responded differently to N-acetyl-chitooligosaccharides, although their plasma membranes all contained a high-affinity binding site for N-acetyl-chitooligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylchitooligosaccharides bind to a specific receptor (Bradley Day et al 2001, Okada et al 2002 and induce membrane depolarization (Kuchitsu et al 1993, Kikuyama et al 1997, ion fluxes , the production of reactive oxygen species (ROS) (Kuchitsu et al 1995) and phytoalexin synthesis West 1992, Yamada et al 1993) in suspension-cultured rice cells. They also elicit lignification in wheat (Barber et al 1989), ion flux and protein phosphorylation in cultured tomato cells (Felix et al 1993), chitinase activity in melon (Roby et al 1987), phenylalanine ammonia-lyase (PAL) and tyrosine ammonia-lyase (TAL) activity in soybean leaves (Khan et al 2003) and glucanase gene transcription in cultured barley cells (Kaku et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chitin perception has been studied in several plants. A K d of 23 nM was described for the binding of a chitin fragment with a degree of polymerization (DP) of 5 to tomato membranes (Baureithel et al, 1994), whereas for membranes from soybean cell cultures and root tissues, K d values between 35 and 75 nM were reported for two chitin ligands (DP 5 5 and DP 5 8; Day et al, 2001) and a K d of 29 nM for rice membranes (Shibuya et al, 1996). In rice cells, a transmembrane chitin oligosaccharide elicitor-binding protein was isolated that carries two extracellular LysM motifs (Kaku et al, 2006).…”
Section: Discussion Fungal Effector Protein Nip1 Interacts With a Sinmentioning
confidence: 99%
“…For the Pep-13 elicitor from P. sojae, 88 fmol 3 mg 21 were found in parsley cells (Nü rnberger et al, 1994), for different elicitins in tobacco, 234 to 403 fmol 3 mg 21 (Bourque et al, 1998), for the hepta-b-glucoside from P. sojae in soybean cells, 1.2 pmol 3 mg 21 (Cheong and Hahn, 1991;Cosio et al, 1998), for chitin fragments in tomato, 2.45 pmol 3 mg 21 (Baureithel et al, 1994), and for soybean cells and roots, 7.6 to 12.2 pmol 3 mg 21 (Day et al, 2001). In comparison, the number of binding sites for the AVR9 elicitor from C. fulvum on tomato membranes is 800 fmol 3 mg 21 (Kooman-Gersmann et al, 1996).…”
Section: The Nip1-binding Site Is Present In Barley and Other Cereal mentioning
confidence: 99%
“…Such patterns correspond to motifs or domains with conserved structural traits found in widely occurring compounds of microbes but not present in their hosts and essential for microbial fitness. High-affinity binding sites in plants have been described for several general elicitors of bacterial, fungal, and oomycete origin, such as flagellin, chitin fragments, a b-heptaglucoside, and cryptogein (Bourque et al, 1999;Gomez-Gomez and Boller, 2000;Bradley Day et al, 2001), and a few of them have been cloned. Four peptides were recently designated as PAMPs in phytopathogenic microorganisms, similar to those involved in the innate immune response in mammals and insects.…”
Section: Introductionmentioning
confidence: 99%